No rising tide : theology, economics, and the future - Rieger, Joerg (Minneapolis : Fortress Press, 2009)
"Even though economic downturns are still followed by upturns, fewer people benefit from them. As a result, economic crisis is an everyday reality that permanently affects all levels of our lives. The logic of downturn, developed in this book, helps make sense of what is going on, as the economy shapes us more deeply than we had ever realized, not only our finances and our work, but also our relationships, our thinking, and even our hopes and desires. Religion is one arena shaped by economics and thus part of the problem but, as Joerg Rieger shows, it might also hold one of the keys for providing alternatives, since it points to energies for transformation and justice. Rieger's hopeful perspective unfolds in stark contrast to an economy and a religion that thrive on mounting inequality and differences of class." -- Publisher's description.
Includes bibliographical references and index.
Keywords: Economics -- Religious aspects -- Christianity; Free enterprise -- Religious aspects -- Christianity